2023
DOI: 10.1088/1361-6463/acc7b2
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure evolution and linear regression fitting models for pre-breakdown electric field strength of FCC, BCC and HCP metal nano-emitters under high electric field from PIC-ED–MD simulations

Abstract: The multi-scale and multi-physics simulations are carried out for the nano-emitters consisting of FCC (Al, Cu and Au), BCC (V, Mo and W) and HCP (Ti, Zn and Zr) metals, using the hybrid electrodynamics coupled with molecular dynamics-particle in cell simulations (PIC-ED-MD). We show that the tilting of nano-emitter at low temperature and small electric field (E-field) is mainly caused either by the movement of partial dislocations at the apex of nanotip or by the elastic local distortions of atomic registries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…In Figures 12D,E, we compare the calculated total field emission current and the local E-field strength of nano-emitter during the whole ED-MD-PIC simulation. The large sparks observed in Figures 12D,E after running simulations for certain times within different treatment of the quantum many-body effects of space charges are an indication of electric prebreakdown caused by structural failure [32][33][34]. In Figure 12D, it is found that the initial emission current is highest for PW-LDA method, The fluctuations seen in Figure 12 for either total emission current or E-field value reflect the changes in atomic structure, shape, and geometries of nano-emitter under the electric stress, thermal stress, and interatomic interactions in typical ED-MD-PIC simulation [32][33][34].…”
Section: Results For 3-d Nanotip In Nano-gapmentioning
confidence: 97%
See 2 more Smart Citations
“…In Figures 12D,E, we compare the calculated total field emission current and the local E-field strength of nano-emitter during the whole ED-MD-PIC simulation. The large sparks observed in Figures 12D,E after running simulations for certain times within different treatment of the quantum many-body effects of space charges are an indication of electric prebreakdown caused by structural failure [32][33][34]. In Figure 12D, it is found that the initial emission current is highest for PW-LDA method, The fluctuations seen in Figure 12 for either total emission current or E-field value reflect the changes in atomic structure, shape, and geometries of nano-emitter under the electric stress, thermal stress, and interatomic interactions in typical ED-MD-PIC simulation [32][33][34].…”
Section: Results For 3-d Nanotip In Nano-gapmentioning
confidence: 97%
“…The large sparks observed in Figures 12D,E after running simulations for certain times within different treatment of the quantum many-body effects of space charges are an indication of electric prebreakdown caused by structural failure [32][33][34]. In Figure 12D, it is found that the initial emission current is highest for PW-LDA method, The fluctuations seen in Figure 12 for either total emission current or E-field value reflect the changes in atomic structure, shape, and geometries of nano-emitter under the electric stress, thermal stress, and interatomic interactions in typical ED-MD-PIC simulation [32][33][34]. Finally, it is worth noting that Cabrera and coworkers systematically studied the current versus voltage characteristics of a diode-like tunnel junctions consisting of a sharp W cathode and a planar electrode as the electron collector with the typical nanogap spacing spanning from 3 nm Frontiers in Physics frontiersin.org to 300 nm and the applied voltage between 10 V and 80 V [48].…”
Section: Results For 3-d Nanotip In Nano-gapmentioning
confidence: 97%
See 1 more Smart Citation